Pengaruh Konsentrasi Naoh Terhadap Kuat Tekan Mortar Geopolimer Abu Terbang Dengan Perawatan Suhu Ruang - Niko Rizaldi; Edy Saputra; Monita Olivia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Geopolymers are environmental friendly construction materials derived from industrial wastes such as fly ash. The use of geopolymers can reduce the use of cement, therefore reducing world carbon emissions. Polymeric bonding in geopolymer fly ash can be activated using alkaline solutions namely Sodium silicate and Sodium hydroxide (NaOH). This study used fly ash from Padang, West Sumatra. The purpose of this study was to examine the effect of the use of fly ash and Sodium hydroxide on the compressive strength of geopolymer mortar. The research method began with the test of the characteristics of fly ash and fine aggregate. Then the fly ash was added to the cement paste with the various concentrations of 8M, 10M, 12M, 14M and 16M NaOH. The size of mold used was the cube of 5 cm x 5 cm x 5 cm. The compressive strength test of mortar was carried out on 7, 14, 28 days of mortar age. The results of this study indicated that the fly ash reacted with NaOH and the compressive strength of mortar geopolymer was influenced by NaOH concentration. The compressive strength of mortar geopolymer showed an increase on specimens that contained 8M, 10M and 12M NaOH. For example, for the use of specimen with 12M NaOH, there was an increased of compressive strength of 16,7% compared to that of specimen with 8M NaOH. On other hand, the compressive strength of specimen containing 14M NaOH and 16M NaOH decreased by 19,6% and 73,21% respectively, compared to that of specimen containing 12M NaOH. The conclusion of this study was the optimum compressive strength occurred on specimens that contained 12M NaOH by 11,2 MPa.Keywords: compressive strength, fly ash, geopolymer, mortar, NaOH concentration